Competitive Strategies and Organizational Performance: Determining the Influential Factor Conquer Over the Rivals in the Food Industry of Bangladesh - Hossain, Md. Shakib; Kabir, Sara Bintey; Mahbub, Nafisa (International Review of Management and Marketing, 2019)
An organization always faces the multifarious challenges like technological evolution, volatile and rigorous demand transformation, economic shifting, and strategic dilemma from its counterpart. Competitive advantages over its counterpart require a massive and propitious strategic direction that surely accomplishing the ultimate desire objectives of an individual organization. This study is mainly incorporated with the different competitive strategies and recognizes how these strategies influence over the organizational performances especial concentration on the food industry in Bangladesh. For identifying the substantial and commensurate circumstance in the food industry a simple random sampling method was used with a sample size of 1025 from the 15 different food manufacturing company. With the concentration of this rigorous work it was observed that competitive strategy has strengthened the organizational performance in the food industry and also noted that cost leadership strategy comparatively propound strategy that helps the firm to consolidate its market share and accelerate its market superiority. Keywords: Competitive advantages, Cost leadership, differentiation strategy, focus strategy, corporate growth strategy, simple random sampling. JEL Classifications: L16, L 22, M 30 DOI: https://doi.org/10.32479/irmm.8109